1979
DOI: 10.1021/es60159a019
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of limestone neutralization of acid waters.

Abstract: In the article, "Kinetics of Limestone Neutralization of Acid Waters" [Environ. Sci. Technoi., 10, 262-6 (1976)], by Paul Barton* and Terdthai Vatanatham, the following corrections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Calcitic limestone (greater than 90% calcite, CaCO 3 ) is by far the most common alkalinity-generating material used in passive treatment. In general, limestone dissolution is self-buffering, providing a pH of about 8 (Barton and Vatanatham, 1976;Rose, 1999), making it is essentially impossible to over treat the ARD. Due to the rapid autooxidation of ferrous iron and low solubility of ferric iron at near-neutral pH, the presence of oxygen and ferric iron in ARD results in the armoring and passivation of limestone.…”
Section: Introductionmentioning
confidence: 99%
“…Calcitic limestone (greater than 90% calcite, CaCO 3 ) is by far the most common alkalinity-generating material used in passive treatment. In general, limestone dissolution is self-buffering, providing a pH of about 8 (Barton and Vatanatham, 1976;Rose, 1999), making it is essentially impossible to over treat the ARD. Due to the rapid autooxidation of ferrous iron and low solubility of ferric iron at near-neutral pH, the presence of oxygen and ferric iron in ARD results in the armoring and passivation of limestone.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by theory since it is well known that heterogeneous (bulk) nucleation rates increase far faster than secondary (growth) rates with increasing supersaturation [10]. Also, Barton and Vatanatham (1976) [13], who quantified the kinetics of the gypsum precipitation reaction, showed that gypsum precipitation in the bulk solution proceeds faster as temperature increases. Smith and Sweet (1971) [14] also found that gypsum precipitation in bulk solution was "too rapid" to study at 90 °C.…”
Section: Effect Of Phmentioning
confidence: 65%
“…Wentzler and Aplan (1972) found that for rapidly rotating disks in which surface coatings were swept oft; calcite dissolution rate actually increased in NazS04 and Fez(S04)J solutions. Barton and Vatanatham (1976) found rates of dissolution were affected by Fe and Al, though most of the effect they observed appears to be due to buffering of pH by Fe and Al precipitation.…”
mentioning
confidence: 86%